Synthetic populations of protoplanetary disks: impact of magnetic fields and radiative transfer - Lebreuilly, Ugo; Hennebelle, P.; Colman, T.; Maury, A.; Tung, N. D.; Testi, L.; Klessen, Ralf S.; Molinari, S.; Commerçon, B.; González, M.; Pacetti, E.; Somigliana, A.; et al. (Astronomy and astrophysics, 2024)
Context: Protostellar disks are the product of angular momentum conservation during protostellar collapse. Understanding their formation is crucial because they are the birthplace of planets and their formation is also tightly related to star formation. Unfortunately, the initial properties of Class 0 disks and their evolution are still poorly constrained both theoretically and observationally. Aims: We aim to better understand the mechanisms that set the statistics of disk properties as well as to study their formation in massive protostellar clumps. We also want to provide the community with synthetic disk populations to better interpret young disk observations. Methods: We used the ramses code to model star and disk formation in massive protostellar clumps with magnetohydrodynamics, including the effect of ambipolar diffusion and radiative transfer as well as stellar radiative feedback. Those simulations, resolved up to the astronomical unit scale, have allowed us to investigate the formation of disk populations. Results: Magnetic fields play a crucial role in disk formation. A weaker initial field leads to larger and massive disks and weakens the stellar radiative feedback by increasing fragmentation. We find that ambipolar diffusion impacts disk and star formation and leads to very different disk magnetic properties. The stellar radiative feedback also have a strong influence, increasing the temperature and reducing fragmentation. Comparing our disk populations with observations reveals that our models with a mass-to-flux ratio of 10 seems to better reproduce observed disk sizes. This also sheds light on a tension between models and observations for the disk masses. Conclusions: The clump properties and physical modeling significantly impact disk populations. It is critical to for the tension, with respect to disk mass estimates, between observations and models to be solved with synthetic observations. This is particularly important in the context of understanding planet formation.
Online veröffentlicht: 30. Januar 2024
Gesehen am 28.06.2024